(untitled) (Research, Society and Development, 2021)
Violence against women is a public health problem, rooted in a gender issue that sees women as an object of submission. Taking into account the high rates of attempted murder and consummated homicide in Brazil and in the world, where this scenario makes it necessary to develop research on the subject. With this, this research aims to investigate the importance of the professional Nurse in the care of victims of domestic violence, as knowledge and preparation of the health professional is necessary when dealing with these situations, which require emotional skill and technical capacity in order to contribute with the possible protection and care of women and the expression of their rights as citizens. The methods adopted were aligned through a quali-quantitative approach, collecting theoretical and field data to arrive at precise results and discuss the points that need to be worked on in the Health System to provide greater support to women. The results showed that most of the participants, despite having considered the care received at the hospital unit adequate, did not consider that they had received any kind of support from nursing professionals, a fact that demonstrates an increasingly intense need for training for nursing professionals. so that they provide adequate humanized care, favoring the patient’s well-being, through the good psychological support provided by the nurse.